Manajemen Operasional dalam Meningkatkan Kualitas Pelayanan Nasabah Perusahaan Asuransi - Siti Fatimah; Adi Syahputra; Muhammad Akbar Fauzan; Murhayati Harahap (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the role of operational management in improving the quality of customer service in insurance companies. The insurance industry faces increasingly complex challenges in the digital era, including changes in customer expectations, intense competition, and the need for operational efficiency. This research employs a systematic literature review method by examining 20 relevant academic articles on operational management and service quality in the insurance sector published between 2021-2026. The findings indicate that the implementation of operational management strategies, including process standardization, digital transformation, employee empowerment, and the application of service quality dimensions (SERVQUAL: tangible, reliability, responsiveness, assurance, and empathy), contributes significantly to improving customer service quality. Based on Saepudin (2023), the assurance dimension has the most dominant influence on customer satisfaction with a coefficient value of 0.387, while Astuti and Taufiq (2023) found that service quality has a more significant effect (coefficient 0.614) than product quality (coefficient 0.210) on customer satisfaction. The success of operational management largely depends on management commitment to service quality, the readiness of human resources, and the integration of information technology. This study concludes that effective operational management is a key determinant in creating customer satisfaction and loyalty in insurance companies.